Greenhouse gas performance and disclosure-new global evidence - Li, Mingchen; Li, Peigong; Zhu, Wanwan (International review of financial analysis, 2025)
This study investigates the relationship between firms' underlying carbon footprints and firms' carbon disclosure for developed economies, developing economies, and internationally as a whole. To provide new evidence, we use an international dataset of firm-level carbon emission and disclosure data from the recently available Carbon Disclosure Project database, as well as other complementary and supplementary data sources. The overall global evidence suggests that firms with greater carbon footprints are associated with more extensive carbon emission-related information disclosure. The result holds for developed economies but not for developing economies. This difference provides new perspectives on connecting the contradictory empirical results that have characterised the prior literature. •In developed economies, there is a negative association between firms' voluntary GHG disclosure and their GHG performance.•In developing economies, firms' voluntary GHG disclosure does not contain any information on their GHG performance.•Disclosed GHG emission figures in firms' own voluntary channels cannot reliably reflect firms’ real GHG performance.•Bad GHG performers are less likely to make their CDP disclosure scores publicly available.